Diagnosis in persistent cerebrospinal fluid fistulas - Duckert, L G; Mathog, R H (The Laryngoscope, 1977)
Cerebrospinal fluid (CSF) rhinorrhea and otorrhea have presented difficult problems in both diagnosis and management; moreover, the threat of impending meningitis necessitates early localization of the source of the leak. The most common techniques for evaluation and isolation of CSF rhinorrhea and otorrhea have included X-ray studies, intrathecal dyes, and radioactive cisternography...